A review of the possibilities of gene doping in sports focused on the advantages and disadvantages - Bara, Sebastian; Barczuk, Patryk; Gałajda, Elżbieta; Antonik, Jacek; Barczak, Iga; Barć, Jan; Kochan, Robert; Bączek, Kacper; Dzięgielewski, Jędrzej; Bondos, Borys (Journal of Education, Health and Sport, 2023)
Introduction and purpose: Gene therapy can be defined as a modification of gene expression in a patient's body. There are two main strategies: the abuse of "classical" gene therapy and strategies of RNA interference with gene transfer. The aim of the study is to analyze scientific literature on gene doping, with a focus on the advantages and disadvantages of using genes related to sports. Materials and methods: The literature available on PubMed was reviewed using the words “gene therapy”, “sport”. Description of the state of knowledge: The potential modification of genes such as EPO, IGF1/GH, HIF-1, PPAR have been identified as having beneficial effects for athletes. Modifying the EPO gene could lead to an increase in red blood cells and oxygen in the blood, which could increase muscle endurance. Modification of the IGF1/GH gene can lead to muscle hypertrophy, block muscle atrophy. The HIF-1 gene codes proteins involved in the hypoxia process and can increase endurance by facilitating the adaptation of cells to low oxygen conditions. Modifying the PPAR gene can impact carbohydrate and lipid metabolism, regulating body mass. Gene therapy could provide a potential cure for diseases such as acute anemia and muscular dystrophy. However, it is important to consider the ethical and health implications of gene doping. Summary: "Gene doping" is a practice that can lead to improved athletic performance but also to serious health problems. The introduction of regulations and doping tests detecting changes in the genome would exclude this practice among athletes who take risky and morally incorrect actions. Increasing the expression of genes such as EPO, IGF-1, HIF-1, PCK1 results in increased muscle endurance and performance. Further research is needed to understand the exact mechanisms and effects of gene therapy. Genetic modification has the potential to bring benefits such as treating diseases such as acute anemia resulting from kidney failure.